2019
DOI: 10.1126/scitranslmed.aau5758
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing fatty acid uptake has therapeutic effects in preclinical models of prostate cancer

Abstract: Metabolism alterations are hallmarks of cancer, but the involvement of lipid metabolism in disease progression is unclear. We investigated the role of lipid metabolism in prostate cancer using tissue from patients with prostate cancer and patient-derived xenograft mouse models. We showed that fatty acid uptake was increased in human prostate cancer and that these fatty acids were directed toward biomass production. These changes were mediated, at least partly, by the fatty acid transporter CD36, which was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
186
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(212 citation statements)
references
References 77 publications
7
186
0
1
Order By: Relevance
“…3B and S3A,B). Recent studies showed that prostate cancer cells show elevated uptake of extracellular fatty acids 4,32 . Our analyses suggest that free fatty acids generated by lipolysis via LIPF can be a potential source of extracellular free fatty acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3B and S3A,B). Recent studies showed that prostate cancer cells show elevated uptake of extracellular fatty acids 4,32 . Our analyses suggest that free fatty acids generated by lipolysis via LIPF can be a potential source of extracellular free fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…Inactivation of fatty acid desaturation creates the need to uptake exogeneous unsaturated fatty acids in order to maintain correct composition of saturated vs. unsaturated lipids in biological membranes 69,71 . Although exogeneous fatty acid uptake has been shown to be important for prostate cancer 4,32 , the relative importance of exogeneous saturated vs. unsaturated fatty acids has not been examined 32 . Our model predicts that malignant cells will be more sensitive to depletion of exogeneous unsaturated fatty acids due to defective endogenous desaturation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, palmitate-induced metastasis of gastric cancer is dependent on CD36, and high CD36 expression levels in gastric cancer patients correlate with poor clinical outcome; therefore, there is a possibility that blocking of the CD36-palmitate axis may serve as a potential gastric cancer treatment [83]. Indeed, CD36 deletion in a prostate cancer animal model revealed a dramatic decrease in fatty acid uptake and ameliorated cancer progression [86]. Immune cells play pivotal roles in regulating tumor progression.…”
Section: Targeting Of Palmitate-induced Pathways As a Therapeutic Strmentioning
confidence: 99%
“…showed promising preclinical efficacy against PCa, unfavourable drug solubility and pharmacokinetics profiles, off-target effects and side effects including weight loss have hindered clinical development of this agent class (14). In addition to de novo synthesis of FAs, PCa cells depend on lipid uptake from the circulation, and from stromal adipocytes (20,41,42). We showed previously that extracellular FAs are the major contributor to lipid synthesis in PCa (22).…”
Section: Targeting Decr1 Suppresses Pca Oncogenesismentioning
confidence: 99%